Jakob Smitsprijs 1981 : Tentoonstelling. - Jakob Smitsmuseum, Mol (Mol : VZW Jakob Smitsprijs, 1981)
Blok, Ernst B.J. ; Booy, Cees ; Bourgeois, Paul ; Couzy, Alfred ; De Coninck, Ludgarde ; De Meyer, Luc ; Dexters, Danielle ; Gastmans, Antoon-Jef ; Ghekiere, Joris ; Goeters, Romain ; Van de Goor, Theodorus ; etc.
Jakob Smitsprijs 1981, Jakob Smitsmuseum, Mol, van 13 december tot 27 december 1981
boek